2022
DOI: 10.1055/a-1731-0332
|View full text |Cite
|
Sign up to set email alerts
|

Lamb Head as a Training Model for Septoplasty and Rhinoplasty

Abstract: Background: Septoplasty and rhinoplasty are difficult operations to learn and teach. Many modalities have been proposed to make the teaching process of these operations easier. In this study, it was investigated if lamb heads were good training models to teach septoplasty and rhinoplasty to trainees or experienced surgeons. Methods: In the first part of the study, 21 lamb heads were dissected according to a dissection protocol and several anatomical distances were measured in order to compare them with human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…They also added that it was not only a tool for beginners, but also a very helpful tool for experienced surgeons to try new surgical methods. 18 In this study, a significant decrease in the septal resistance was observed after one-sided elevation of the mucoperichondrium except for the key area and middle vault. The elevation of the left side was performed after resection of the nasal septum which showed no effect on the septal resistance significantly.…”
Section: Discussionsupporting
confidence: 45%
“…They also added that it was not only a tool for beginners, but also a very helpful tool for experienced surgeons to try new surgical methods. 18 In this study, a significant decrease in the septal resistance was observed after one-sided elevation of the mucoperichondrium except for the key area and middle vault. The elevation of the left side was performed after resection of the nasal septum which showed no effect on the septal resistance significantly.…”
Section: Discussionsupporting
confidence: 45%
“…strut biodynamics in previous studies, stating that it is not only a tool for beginners, but also a very useful tool for experienced surgeons on which to try new surgical methods 14,22 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Apaydın et al supported the use of lamb heads as training models for septoplasty and rhinoplasty due to their low cost, easy accessibility, and close resemblance to human cadavers. Furthermore, lamb heads have been used in endoscopic sinus surgery, DSR and osteotomy models in literature, and all studies emphasize its usefulness especially for resident training [21][22][23][24][25] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations